Multilingual Codeswitching in Quebec Rap: Poetry, Pragmatics and Performativity - Sarkar, Mela; Winer, Lise (International Journal of Multilingualism, 2006)

‘Ch'us mon propre Bescherelle’: Challenges from the Hip-Hop nation to the Quebec nation - Low, Bronwen; Sarkar, Mela; Winer, Lise (Journal of Sociolinguistics, 2009)
We examine the uses of and attitudes towards language of members of the Montreal Hip-Hop community in relation to Quebec language-in-education policies. These policies, implemented in the 1970s, have ensured that French has become the common public language of an ethnically diverse young adult population in Montreal. We argue, using Blommaert's (2005) model of orders of indexicality, that the dominant language hierarchy orders established by government policy have been both flattened and reordered by members of the Montreal Hip-Hop community, whose multilingual lyrics insist: (1) that while French is the lingua franca, it is a much more inclusive category which includes ‘Bad French,’ regional and class dialects, and European French; and (2) that all languages spoken by community members are valuable as linguistic resources for creativity and communication with multiple audiences. We draw from a database which includes interviews with and lyrics from rappers of Haitian, Latin-American, African-American and Québécois origin.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1467-9841.2008.00393.x
Keywords: Order of indexicalities; Quebec language policy; multilingual code-switching; normative tradition (French); rap lyrics; urban youth culture

"Pour connecter avec le peeps": Québéquicité and the Quebec Hip-Hop Community - Sarkar, Mela; Low, Bronwen; Winer, Lise (Identity and Second Language Learning: Culture, Inquiry, and Dialogic Activity in Educational Contexts, 2006)

Multilingual code-switching in Montreal Hip-Hop: Mayhem meets method, or, ‘Tout moune qui talk trash kiss mon black ass du nord’ - Sarkar, Mela; Winer, Lise; Sarkar, Kobir (ISB4: Proceedings of the 4th International Symposium on Bilingualism, 2005)